Provide optimal strategies in coastal architecture of Kish island to deal with future environmental consequences - Moshabaki Isfahani, Ali Reza; Etesam, Iraj; Majedi, Hamid; Mokhtabad Amreei, Seyed Mostafa (Nexo Revista Científica, 2021)
The purpose of this study is to design and explain a prospective model for measuring tourism sustainability in Kish Island. Accordingly, the conceptualization of coastal architecture or tourism, the identification of influential factors and operational strategies for improving the tourism industry, especially on the coastal dimensions of the island, have been considered. Due to the exploratory nature of the research, the strategy used in this research is Grounded theory. The sampling used in this study was theoretical sampling. The main basis for gathering information has been to conduct in-depth interviews with managers and senior experts in coastal tourism to reach theoretical saturation. A total of 13 interviews were conducted. After gathering information, the written interview codes were analyzed. The findings were coded according to the paradigmatic pattern of Strauss and Corbin. Therefore, after performing the three steps of open, axial and selective coding, final modeling was achieved. The model consists of 6 general categories (causal, contextual, interventionist, pivotal, strategies and consequences) and 12 subcategories and 36 semantic concepts and data.